Pengaruh Kebijakan Besarnya Dividen Terhadap Harga Saham Perusahaan - Phan Krishandani dan Ignatius Roni Setyawan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this study was to determine the effect of policy on the amount of dividends on the stock price of companies listed on the Indonesian stock exchange. The determinants tested in this study are dividend policy. the object in this study is the stock price of the companies incorporated in LQ - 45 for the period 2006 to 2008. Subjects in this study are companies incorporated in LQ - 45 engaged in the financial industry, there are 10 companies in 2006 to 2008 that meet the criteria used as a sample. The data used is secondary data collected from the company's financial statements. the method used in this research is analytical descriptive method, to describe data, facts, traits and relationships that occur systematically, factually and accurately. The results of this study indicate that the dividend policy has a significant effect on the company's stock price of 78.2%, while the rest is influenced by other variables.